PERSEPSI DAN PARTISIPASI MASYARAKAT TERHADAP PROGRAM PENGEMBANGAN BIOGAS DI KECAMATAN TAMBAN CATUR KABUPATEN KAPUAS - Tati Inderawati; Danang Biyatmoko; Muhammad Rizal; Lilis Hartati (Universitas Lambung Mangkurat, 2016)
Biogas is a renewable energy source needed as an alternative potential fuel. This research aims to 1) analyse perceptions and participations of community to the development of biogas in Kecamatan Tamban Catur, Kabupaten Kapuas, 2) identify factors influencing the success of biogas development in Kecamatan Tamban Catur, Kabupaten Kapuas, and 3) analyse the benefits of using biogas for community in Kecamatan Tamban Catur, Kabupaten Kapuas. The research was carried out in Sidomulyo, Sidorejo, and Warnasari Villages in Kecamatan Tamban Catur, Kapuas Regency. The research was conducted using survey data, and the data were further analyzed through descriptive statistics involving 33 respondents who have received the program of biogas development in Kecamatan Tamban Catur Kapuas Regency. The dependent variables were perceptions and participations of community while the independent variables were ages, the number of cattle, education, supporting program, and duration of biogas utilization. The results indicated that community perceptions of the biogas development were positively increasing (78.8%). The F-Test showed that independent variables influencing community perceptions significantly (P<0.05) with 35.1% of coefficient determination (R2). Although community participations to biogas development were relatively high (72.7%), there was no apparent impact (P>0.05) of independent variables to the community participations. Factors influencing the success of biogas development in Kecamatan Tamban Catur were passion, the number of cattle, floor types, applicable technology, and supporting programs from the government agencies. There are several advantages of using biogas for the community. First, the use of biogas improves cost efficiency per month by reducing the usage of fuel/kerosene for about 15 liters (Rp.150.000,-) and the usage of 60 bundles of fire-wood (Rp.120.000,-). Moreover, utilizing solid and liquid organic fertilizer increased daily income for Rp. 10.000,- and Rp. 48.000,- respectively. In addition, biogas application is more environmentally-friendly.